(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Implementing learning program accreditation (CTDT) to meet the ASEAN University Network – Quality Assurance (AUN – QA) criterions/criteria at educational institutions is increasing daily/day by day. It comes from the inevitable need to train human recruitment to serve the country’s socio-economic development and international integration requirement. Collecting information directly from lecturers who evaluate learning programs at educational institutions is objective evidence, providing authentic information that reflects the training quality. Objective: Determine the rate of good evaluation of lecturers the healthcare sector learning program at universities in Vietnam universities which meet AUN - QA standards. Methods: Cross-sectional description of 228 lecturers teaching in the health sector at universities in Vietnam meeting AUN - QA standards. Results: Lecturers’ evaluation of the training program in 7 specific contents is: Regarding output standards, the good level is 97.4%; Regarding the curriculum description, the good level reached 91.7%; Regarding the structure and content of the curriculum, the good level reached 81.1%; Regarding teaching and learning methods, the good level reached 90.4%; Regarding classroom organization, the good level reached 53.1%; Regarding impact factors, the good level reached 54.8%; Regarding learners, the good level reached 78.5%. The lecturers’ overall assessment of the learning program is at a good level, reaching 77.2%. Conclusion: Evaluation from lecturers on the learning program is at a good level of 77.2%.